2018
DOI: 10.17240/aibuefd.2018..-431421
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Dönemde Okula Uyum Süreci̇ne İli̇şki̇n Öğretmen Görüşleri̇

Abstract: ÖZETBu araştırmanın amacı, okulöncesi dönemde okula uyum sürecinde uygulanan stratejiler ve karşılaşılan sorunlar hakkında öğretmen görüşlerinin incelemektir. Ayrıca okula uyum sürecinde devlet okullarında uygulanan stratejiler ile özel okullarda uygulanan stratejiler arasında farklılık olup olmadığı da belirlenmeye çalışılmıştır. Bu amaç doğrultusunda; nitel araştırma yöntemlerinden tipik durum çalışması yoluyla gerçekleştirilmiştir. Araştırmanın çalışma grubunu beşi devlet kurumunda, beşi özel kurumda görev … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…This finding is supported by previous evidence in the literature (Bağçeli et al, 2018;Türker Üçüncü & Aktan Acar, 2021;Mercan Uzun & Bütün, 2016;Başal et al, 2019;Karoly & Gonzalez, 2011). For example, it has been found that refugee children who have problems in adaptation to school experience introversion in addition to behavior and adaptation problems (Bağçeli et al, 2018;Polat Uluocak, 2009). One of the findings of the study is that exclusion is a problem that refugee children face in the process of adaptation to school.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding is supported by previous evidence in the literature (Bağçeli et al, 2018;Türker Üçüncü & Aktan Acar, 2021;Mercan Uzun & Bütün, 2016;Başal et al, 2019;Karoly & Gonzalez, 2011). For example, it has been found that refugee children who have problems in adaptation to school experience introversion in addition to behavior and adaptation problems (Bağçeli et al, 2018;Polat Uluocak, 2009). One of the findings of the study is that exclusion is a problem that refugee children face in the process of adaptation to school.…”
Section: Discussionsupporting
confidence: 81%
“…The negative attitude and behavior exhibited by refugee families also affects children's adaptation processes to school. Previous studies (Bağçeli et al, 2018;Yanık Özger & Akansel, 2019) emphasized that the families play an important role in the adaptation processes of children to school. In line with the results of this study, the fact that refugee families do not find it necessary to learn Turkish and think that they are in Turkey temporarily, that families do not show enough interest in their children and that only the school is responsible for their children's education makes it difficult for their children to adapt to school (Rah, Choi, & Nguyễn, 2009;Yanık Özger & Akansel, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bronfenbrenner emphasizes that this transition between home and school and the adaptation to school, plays an important role in the development of the child in the ecological systems model [17]. The ecological model argues that children's transition to school should be successfully shaped by the support provided by the family at home, and by the teacher at school [18,19]. In this process, it is thought that the relationship established between the teacher and child influences school adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of adaptation to school, the child should be made to feel comfortable in the classroom, loved, and made to love himself/herself. The teacher should also have empathic communication with the child and be patient and tolerant [2,18,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…İlgili alanyazın incelendiğinde araştırmaların genellikle diğer branşlarda görev yapan öğretmenlerin yaşadıkları sorunlara yönelik olduğu görülmektedir (Afşin, 1988;Erdemir, 2007;Ergenekon, 2004;Erkoç, 2010;Hamarat, 2002;Korkmaz, 1999;Korkmaz, Saban ve Akbaşlı, 2004;Kösterelioğlu ve Kösterelioğlu, 2008;Öztürk, 2016;Sarı ve Altun, 2015). Okul öncesi öğretmenlerinin yaşadıkları sorunların belirlenmesi ile ilgili yalnız birkaç araştırmaya rastlanırken (Aktankerem ve Cömert, 2006;Bağçeli-Karaman, Şen, Alataş ve Tütüncü, 2018;Başturan, 2018;Başaran, Gökmen ve Akdağ, 2014;Demircan-Aydın, 2017;Erden, 2010;Kaplan, 2015;Kök, Küçükoğlu, Tuğluk ve Koçyiğit, 2007;Zembat, 2012), okul öncesi öğretmenlerinin ilk yıllardaki mesleki deneyimlerine yönelik bir çalışmaya rastlanamamıştır. Bu nedenle bu araştırmanın amacı, okul öncesi öğretmenlerinin meslek yaşantılarının ilk yıllarına ilişkin deneyimlerinin neler olduğunu ortaya çıkarmaktır.…”
unclassified